Engineering Innovations Vol. 5 - Jav Davaasambuu; Ian McAndrew; Katsuyuki Kida; Dong Keon Kim (Trans Tech Publications Ltd, 2023)
The 5th volume of'Engineering Innovations'included articles based on research results in materials science, building construction, machine designing and defect monitoring, some technologies and materials for environmental protection and bioreactor parameters identification. Engineers, technologists, academics, and students will appreciate the articles presented.